The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s40264-022-01151-w
|View full text |Cite
|
Sign up to set email alerts
|

Description of Frequencies of Reported Adverse Events Following Immunization Among Four Different COVID-19 Vaccine Brands

Abstract: Introduction The rapid rollout of coronavirus disease 2019 (COVID-19) vaccines for a large proportion of the population necessitates a strong emphasis on safety. Complementary to the existing spontaneous reporting system, The Netherlands Pharmacovigilance Centre Lareb conducted patient-reported cohort event monitoring (CEM). Objective The primary aim was to investigate differences in the frequencies of any and commonly reported, ‘well-known’, systemic adverse events fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
6
31
0
1
Order By: Relevance
“…29 Our study revealed that most of the post-COVID-19 vaccination adverse events were low to moderate in severity and were not severe enough to require hospitalization and usually resolved within a few days after vaccination and the same trend was reported in several studies. 15,22,25,29 The present study also showed that the reported adverse events were significantly higher among female participants and those who received AstraZeneca vaccination with multivariable-adjusted OR (95% CI) of 2.26 (1.67-3.08) and 4.31 (2.85-6.51), respectively. Gender differences were observed in different studies on different populations with females being more prone to report the occurrence of post-COVID-19 vaccination adverse events than males e.g., Menni and 20 Moreover, a two-phased randomized clinical trial that was conducted in China on Sinopharm vaccine, exhibited more common adverse events in females (55%) compared to males (45%).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…29 Our study revealed that most of the post-COVID-19 vaccination adverse events were low to moderate in severity and were not severe enough to require hospitalization and usually resolved within a few days after vaccination and the same trend was reported in several studies. 15,22,25,29 The present study also showed that the reported adverse events were significantly higher among female participants and those who received AstraZeneca vaccination with multivariable-adjusted OR (95% CI) of 2.26 (1.67-3.08) and 4.31 (2.85-6.51), respectively. Gender differences were observed in different studies on different populations with females being more prone to report the occurrence of post-COVID-19 vaccination adverse events than males e.g., Menni and 20 Moreover, a two-phased randomized clinical trial that was conducted in China on Sinopharm vaccine, exhibited more common adverse events in females (55%) compared to males (45%).…”
Section: Discussionsupporting
confidence: 63%
“…However, a recent study in Netherlands reported that Pfizer-BioNTech was the most utilized vaccine type followed by AstraZeneca. 15 Despite that 84% of the Egyptian participants who received two doses of vaccine, 32% and 26.7 % of them, respectively, were hesitant and unwilling to receive a COVID-19 booster vaccine. The proportions were much higher than reported by Paul and Fancourt (2021) who found that among fully vaccinated adults in the UK only 4% were uncertain about receiving and 4% were unwilling to receive a COVID-19 booster vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, higher number of patients who took ChAdOx1 developed series AEFI compared to patients who took Moderna and Pfizer vaccine. 35 Another study finding indicate that among all immunized individuals more than half (58.1%) of the AEFI, and nearly half (49.5%) of severe adverse events were reported following ChAdOx1 vaccination compared to Moderna and Pfizer vaccines. 36 …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is strengthened by a descriptive study of the frequency of adverse events reported after COVID-19 vaccination, where the rate of ADRs reported was lower with mRNA vaccines than with live non-replicating vaccines (rate of adverse effects reported after the first injection: 92.2% with ChAdOx1 nCov-19; 82.0% with Ad26COV2.S vs . 81.7% with mRNA-1273 and 45.2% with Bnt162b2) ( Kant et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%